REER misalignment and economic growth in the CAEMC Region - Mohamadou, Baba (Research of GSB, 2018)
The CFA Franc real exchange rate is frequently suspected to be overvalued as a result of recent prolonged appreciation of the Euro (the anchor currency). This situation is popularly associated with lose of competitiveness and several studies have tried to establish the relationship between growth and misaligned or overvalued real exchange rates. This study used a panel data cointegration techniques to evaluate the growth effects of real effective exchange rate misalignments for the Central African Economic and Monetary Community (CAEMC) using time series data from 1999-2010. To achieve this objective, the Real Effective Equilibrium Exchange Rate for the CFA Franc was first estimated using the Behavioural Equilibrium Exchange Rate (BEER) from which the misalignment was derived. Subsequently, a dynamic panel growth model was estimated using a Generalised Least Squares (GLS) Method, in which among the traditional determinants of growth, our measure of misalignment was included. Moderate and transitory misalignments were found for the six CAEMC member countries except for the Congo Republic were a sustained overvaluation was observed. The growth analysis indicates a positive and significant impact of real exchange rate misalignment to economic growth of the CAEMC member countries.